1984
DOI: 10.1136/adc.59.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Perinatal lead and cadmium burden in a British urban population.

Abstract: SUMMARY Concentrations of the potential pollutants, lead and cadmium, were studied in the perinatal period in a British urban population. Blood lead and cadmium concentrations and iron status were measured in 28 mother and infant pairs at delivery and at five days postpartum in the mother; breast milk collected at five days postpartum under controlled conditions was analysed for lead and cadmium. Placental transfer of both metals was noted; concentrations of lead in breast milk (mean concentration 0.01 mmol/l … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
1

Year Published

1986
1986
2019
2019

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(8 citation statements)
references
References 14 publications
0
7
1
Order By: Relevance
“…As cigarette smoking is one of the main predictors of blood Cd levels, 22,85 these disparities may reflect a decline in cigarette smoking in developed countries. The mean level of blood Cd is slightly lower than that reported by Kovar et al 86 in the UK (0.69 ± 0.65 µg/l), although their sample size was very small (n = 28).…”
Section: Cadmiumcontrasting
confidence: 72%
“…As cigarette smoking is one of the main predictors of blood Cd levels, 22,85 these disparities may reflect a decline in cigarette smoking in developed countries. The mean level of blood Cd is slightly lower than that reported by Kovar et al 86 in the UK (0.69 ± 0.65 µg/l), although their sample size was very small (n = 28).…”
Section: Cadmiumcontrasting
confidence: 72%
“…Casey (1977) analysed cows' milk and cows' milk-derived infant formulas and found that Pb concentrations in these samples were consistently higher than those found in breast milk. Moreover, higher Pb concentrations in formulas than in breast milk were observed in New Zealand (Casey, 1977), Thailand (Chatranon et al 1978), the UK (Kovar et al 1984;Richmond et al 1993), India (Tripathi et al 1999), Spain (Rodriguez Rodriguez et al 1999;Martino et al 2001), Australia (Gulson et al 2001) and Canada (Hanning et al 2003). In industrial regions of Austria (Styria), the range of Pb concentration (0 -20•4 ng Pb/g) in human milk was lower than in formulas (0 -35•4 ng Pb/g) (Tiran et al 1994).…”
Section: Formula Use Increases Exposure Risksmentioning
confidence: 99%
“…The World Health Organization estimates that there are now 235 million asthmatics worldwide [ 1 ] and more than 17 million of this individuals are in the United States [ 2 ]. In Morocco, 3.89% of the Moroccan population was affected by asthma, in 2009, which represents more than 1.2 millions people [ 3 ].…”
Section: Introductionmentioning
confidence: 99%